The Relationship between Mindfulness and Resilience with Psychological Adaptation: The Mediating Role of Locus of Control in Women with Cancer - MollaAli Farkhani, Shirin; Famil Zavar Jalali, Akram Sadat; Kamali Nejad, Masoomeh (Journal of Assessment and Research in Applied Counseling (JARAC), 2024)
Objective: This article examines the relationship between mindfulness and resilience with psychological adaptation in women diagnosed with cancer. The objective of this study is to determine the mediating role of Locus of Control in this relationship. Methods and Materials: The research method used was descriptive correlational modeling (structural equations). Participants in this study were women with cancer visiting all treatment centers (hospitals and private and public clinics) in Tehran, among whom 206 individuals were selected through convenience sampling. Findings: The results of statistical analyses indicated that Locus of Control significantly mediates the relationship between mindfulness and resilience with psychological adaptation. Conclusion: These findings can assist in designing intervention programs that support women with cancer in enhancing their mindfulness and resilience, thereby aiding in improving their psychological adaptation. It is recommended that future studies be conducted on larger and more diverse samples to gain a deeper understanding of these phenomena. Additionally, examining the role of other mediating factors such as social support and spirituality may help complete the overall picture.